A simple method to derive speed for the endurance shuttle walk test - Hill, Kylie; Dolmage, T.; Woon, L.; Coutts, D.; Goldstein, R.; Brooks, D. (WB Saunders Co Ltd, 2012)
Background: The original method for determining endurance shuttle walk test (ESWT) speed involves components that are time consuming for clinicians. We sought to determine: (i) whether components described in the original method for determining ESWT speed held true and; (ii) the agreement between speeds derived using the original method and that equivalent to 85% of the peak speed achieved during the incremental shuttle walk test (ISWT). Methods: Patients with chronic obstructive pulmonary disease (COPD) performed two ISWTs and one ESWT on separate days, wearing a calibrated portable gas analysis unit. A retrospective analysis of these data allowed us to determine whether: (i) the peak rate of oxygen uptake (VO2peak) can be accurately estimated from the incremental shuttle walk distance (ISWD) and; (ii) ESWTs performed at a speed derived using the original method elicited 85% of VO2peak. Agreement between walks speeds was determined using Bland–Altman analysis. Results: Twenty-two participants (FEV1 48 ± 13% predicted, age 66 ± 8 yr) completed the study. The VO2peak estimated from the ISWD was less than that measured during the ISWT (mean difference −4.4; 95% confidence interval (CI), −6.0 to −2.9 ml• kg−1•min−1). The ESWT and ISWT elicited similar VO2peak (mean difference −0.2; 95% CI, −1.5 to 1.2 ml•kg−1•min−1). The mean difference (±limits of agreement) between ESWT speeds was 0.15 (±0.34) km•h−1. Conclusions: Components of the original method for determining the ESWT speed did not hold true in our sample. ESWT speed can be derived by calculating 85% of the peak speed achieved during the ISWT.